Chemically Assisted Enucleation Results in Higher G6PD Expression in Early Bovine Female Embryos Obtained by Somatic Cell Nuclear Transfer - Saraiva, Naiara Zoccal [UNESP]; Oliveira, Clara Slade [UNESP]; Drummond Tetzner, Tatiane Almeida [UNESP]; de Lima, Marina Ragagnin [UNESP]; de Melo, Danilas Salinet [UNESP]; Meo Niciura, Simone Cristina; Garcia, Joaquim Mansano [UNESP] (Mary Ann Liebert, Inc., 2012)
Despite extensive efforts, low efficiency is still an issue in bovine somatic cell nuclear transfer (SCNT). The hypothesis of our study was that the use of cytoplasts produced by chemically assisted enucleation (EN) would improve nuclear reprogramming in nuclear transfer (NT)-derived embryos because it results in lower damage and higher cytoplasm content than conventional EN. For that purpose, we investigated the expression of two X-linked genes: X inactive-specific transcript (XIST) and glucose 6-phosphate dehydrogenase (G6PD). In the first experiment, gene expression was assessed in day-7 female blastocysts from embryonic cell NT (ECNT) groups [conventional, ECNT conv; chemically assisted, ECNT deme (demecolcine)]. Whereas in the ECNT conv group, only one embryo (25%; n = 4) expressed XIST transcripts, most embryos showed XIST expression (75%; n = 4) in the ECNT deme group. However, no significant differences in transcript abundance of XIST and G6PD were found when comparing the embryos from all groups. In a second experiment using somatic cells as nuclear donors, we evaluated gene expression profiles in female SCNT-derived embryos. No significant differences in relative abundance (RA) of XIST transcripts were observed among the groups. Nonetheless, higher (p < 0.05) levels of G6PD were observed in SCNT deme and in vitro-derived groups in comparison to SCNT conv. To know whether higher G6PD expression in embryos derived from SCNT chemically assisted EN indicates higher metabolism in embryos considered of superior quality or if the presence of higher reactive oxygen species (ROS) levels generated by the increased oxygen consumption triggers G6PD activation, the expression of genes related to stress response should be investigated in embryos produced by that technique.